FDI NEXUS TERRORISM: Evidence from Pakistan - Jan, Muhammad Shabir; Nisar, Muhammad; Zubair, Seema; Hanan, Fazal; Khan, Muhammad Taimur; Ali, Liaqat; Rahman, Zia Ur; khan, Azhar (The journal of contemporary issues in business and government, 2021)
The study conduct to determine the co-integration between the FDI and terrorism. Time series data. The data for terrorism is taken form World Governances Indicator WGI and Foreign Direct Investment (FDI) data is taken from world bank. The study applied the co-integration and granger causality test to check the causality between terrorism and foreign Direct Investment (FDI). The study applied the ADF unit root test, co-integration and granger causality test the result concluded that variable are stationary at difference so the variable are not co-integrate means that the FDI and terrorism does not a granger causality of each other.